Alveolar bone loss induced by high alcohol consumption in rats - Souza, Daniela Martins de; Silva, Alan de Aquino; Pereira, Kauê Alberto; Gonsalves, Vitor Sulz; Rodrigues, Vinicius Anéas; Carvalho, Claudemir de Carvalho de (Brazilian Dental Science, 2017)
Objective: The aim of the present study was to assess the effect of regular and constant long-term alcohol consumption on the percentage of the remaining periodontal bone support (PBS) and periodontal bone loss (PBL) in adult rats. Material and Methods: Fifty-four (54) rats were divided into 3 groups: Control (daily water intake, n=18) daily alcohol intake (20% ethanol, n=18) and social alcohol intake (20% ethanol 2x a week, n=18). The rats were treated with continuous free-choice access to both ethanol consumption frequencies. They were euthanized after 90 days and their left mandibles were radiographed for PBS measuring. The same left mandibles were defleshed and stained. The PBL was morphometrically assessed by measuring the distance between cement-enamel junction and alveolar bone crest. Results: Did not show difference (p > 0.05) in the amount of consumed alcohol between the social and daily intake groups. Rats also evidenced lower PBS percentage and higher PBL (p